2008
DOI: 10.1038/sj.ejhg.5202008
|View full text |Cite
|
Sign up to set email alerts
|

HHEX gene polymorphisms are associated with type 2 diabetes in the Dutch Breda cohort

Abstract: Recently, the hematopoietically expressed homeobox (HHEX) gene, encoding a transcription factor, was identified in a large genome-wide scan in French individuals as a type 2 diabetes (T2D)-susceptibility locus. We aimed to check whether this finding could be replicated in a Dutch T2D cohort. Two common variants (rs7923837 and rs1111875) located near the HHEX gene were genotyped in 501 unrelated T2D patients and in 920 healthy controls. The major alleles of both variants were overrepresented in T2D cases compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…22,23,30,31 On the other hand, the association study and meta-analysis further confirmed the effect of HHEX rs1111875 on type 2 diabetes in Chinese population, consistent with previous genome-wide association studies and replication studies in other ethnic populations. [15][16][17][18][19]25,26,[32][33][34] The HHEX gene encodes a transcription factor that is also involved in the Wnt signaling pathway and that has been shown to be essential for pancreas development. van Vliet-Ostaptchouk et al 19 suggested that HHEX was the most likely causal candidate in chromosome 10q.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22,23,30,31 On the other hand, the association study and meta-analysis further confirmed the effect of HHEX rs1111875 on type 2 diabetes in Chinese population, consistent with previous genome-wide association studies and replication studies in other ethnic populations. [15][16][17][18][19]25,26,[32][33][34] The HHEX gene encodes a transcription factor that is also involved in the Wnt signaling pathway and that has been shown to be essential for pancreas development. van Vliet-Ostaptchouk et al 19 suggested that HHEX was the most likely causal candidate in chromosome 10q.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19]25,26,[32][33][34] The HHEX gene encodes a transcription factor that is also involved in the Wnt signaling pathway and that has been shown to be essential for pancreas development. van Vliet-Ostaptchouk et al 19 suggested that HHEX was the most likely causal candidate in chromosome 10q. However, in our study, both IDE rs11187007 and HHEX rs1111875 were detected to be associated with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2007, the rs1111875C in the HHEX gene was reported to be associated with T2DM in Finland and Sweden populations [18]. In 2008, Jana et al [35] conducted an association study, their data con rmed the association of the common variant rs1111875C in the HHEX gene, identi ed by Sladek et al [36] in French population, with an increased risk of T2DM in a Dutch population. In 2008, Wu et al reported that the associations of the HHEX rs1111875C allele with T2DM in Chinese Shanghai population [14].…”
Section: Discussionmentioning
confidence: 98%
“…Several studies also reported associations between rs1111875 and rs7923837 and fasting insulin secretion, insulin sensitivity and insulin secretion response following a glucose load [28][32]. Therefore, HHEX was suggested as the most likely causal candidate gene at 10q23.33 for type 2 diabetes [33]. Nevertheless, IDE is also another strong candidate gene.…”
Section: Discussionmentioning
confidence: 99%